Occupational solvent exposure during pregnancy and child behaviour at age 2. Issue 2 (30th October 2012) - Pelé, Fabienne; Muckle, Gina; Costet, Nathalie; Garlantézec, Ronan; Monfort, Christine; Multigner, Luc; Rouget, Florence; Cordier, Sylvaine
Abstract : Objectives: Many women who work during pregnancy are occupationally exposed to toxicants. The developing central nervous system is highly vulnerable to neurotoxicants such as solvents. Although the neurotoxicity of solvents to adults is well established, very few studies have examined their effects on children's behaviour following prenatal exposure. Methods: Women from the Perturbateurs endocriniens: Étude Longitudinale sur les Anomalies de la Grossesse, l'Infertilité et l'Enfance (PELAGIE) mother–child cohort (including 3005 working women) were recruited in Brittany (France) between 2002 and 2006, at the beginning of pregnancy, to assess occupational exposure to solvents at that time. Child behaviour was documented at age 2 by mothers (n=1278) assessing components of attention deficit/hyperactivity, aggression, opposition and emotionality. We used a multiple linear regression analysis to evaluate the association between occupational solvent exposure and children's behaviour. Complementary sensitivity analyses allowed us to handle missing data, due mostly to attrition. Results: 20% of women reported occasional exposure and 31% regular exposure to solvents. Children prenatally exposed were more likely to have higher scores of attention deficit/hyperactivity and aggression, and dose–response relations were observed. Conclusions: The dose–response effect and the high prevalence of children potentially exposed to solvents from their mother's workplace exposure underline the public health relevance of this result. Our results should be replicated in further studies designed to identify which solvents are most deleterious and to assess child behaviour at school age.